2009
DOI: 10.1063/1.3074779
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric properties and nanoscale structure of Fe-doped Gd5Ge2Si2 alloys

Abstract: Articles you may be interested inLow hysteresis and large room temperature magnetocaloric effect of Gd5Si2.05− x Ge1.95− x Ni2 x (2x = 0.08, 0.1) alloys J. Appl. Phys. 113, 17A916 (2013); 10.1063/1.4795434The giant magnetocaloric effect of Gd 5 Si 1.95 Ge 2.05 enhanced by Sn doping

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The MCE results from changes in the magnetic order of materials, with the most optimum MCE near the was found to increase when Fe was substituted for Ge but it rather decreased rapidly when it was substituted for Si as can be seen in Table 3 [30]. However, in the case of doping the same amount of either Ni or Bi had a negligible effect on the magnetocaloric properties [26,27].…”
Section: Gd(si Ge) Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCE results from changes in the magnetic order of materials, with the most optimum MCE near the was found to increase when Fe was substituted for Ge but it rather decreased rapidly when it was substituted for Si as can be seen in Table 3 [30]. However, in the case of doping the same amount of either Ni or Bi had a negligible effect on the magnetocaloric properties [26,27].…”
Section: Gd(si Ge) Alloysmentioning
confidence: 99%
“…Though most investigation were made for Ge substitution, a significant reduction in Δ|S M | because of the suppression of the structural transformation has been observed so it is suggested that Si and Ge should be substituted simultaneously for Fe and Sn doping as can be seen in Table 3 [15,[28][29][30][31]. A small substitution with iron (substituting for 5% of the germanium, otherwise it will have deleterious effect on MCE properties and minimal effect on reducing hysteresis losses [28,30]) reduced the losses by 90% thus resulting in 20%-50% higher RCP value, though it overall reduced the Δ|S M | to only one-third of its original value [27,29,30]. The T C of the matrix phase cess.…”
mentioning
confidence: 99%